Accumulation Rates during 1311–2011 CE in North-Central Greenland Derived from Air-Borne Radar Data - Karlsson, Nanna B.; Eisen, Olaf; Dahl-Jensen, Dorthe; Freitag, Johannes; Kipfstuhl, Sepp; Lewis, Cameron; Nielsen, Lisbeth T.; Paden, John D.; Winter, Anna; Wilhelms, Frank (Frontiers in Earth Science, 2016)
Radar–detected internal layering contains information on past accumulation rates and patterns. In this study, we assume that the radar layers are isochrones, and use the layer stratigraphy in combination with ice-core measurements and numerical methods to retrieve accumulation information for the northern part of central Greenland. Measurements of the dielectric properties of an ice core from the NEEM (North Greenland Eemian Ice Drilling) site, allow for correlation of the radar layers with volcanic horizons to obtain an accurate age of the layers. We obtain accumulation patterns averaged over 100 a for the period 1311–2011. Our results show a clear trend of high accumulation rates west of the ice divide and low accumulation rates east of the ice divide. At the NEEM site the accumulation pattern is persistent during our study period and only small temporal variations occur in the accumulation rate. However, from approximately 200 km south of the NEEM drill site, the accumulation rate shows temporal variations based on our centennial averages. We attribute this variation to shifts in the location of the high–low accumulation boundary that usually is aligned with the ice divide, but appears to have moved across the divide in the past.